2023
DOI: 10.1021/acscatal.2c06300
|View full text |Cite
|
Sign up to set email alerts
|

Steric Parameterization Delivers a Reciprocally Predictive Model for Substrate Reactivity and Catalyst Turnover in Rh-Catalyzed Diyne-Alkyne [2 + 2 + 2] Cycloadditions

Abstract: The Rh-catalyzed [2 + 2 + 2] cycloaddition of diynes and alkynes is a synthetically useful transformation that rapidly constructs complex scaffolds and has been used extensively for >70 years. Despite this utility, substrate reactivity issues persist, which are not mechanistically defined. Here, we provide a general predictive model for reactivity and turnover for this reaction. Contrary to the proposed electronic model, this is a predominately sterically driven process where productive turnover is proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…This is directly related to the steric footprint of the BMIDA unit, which restricts catalytic turnover as previously described ( vide infra ). 32 BINAP was the optimal ligand, with other ligands significantly less effective ( e.g. , entries 2 and 3).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…This is directly related to the steric footprint of the BMIDA unit, which restricts catalytic turnover as previously described ( vide infra ). 32 BINAP was the optimal ligand, with other ligands significantly less effective ( e.g. , entries 2 and 3).…”
mentioning
confidence: 96%
“…A key limitation of this strategy is associated with a long-standing problem in semi-intermolecular [2+2+2] cycloaddition where internal alkynes are not tolerated unless they have coordinating groups. 32–34 With borylated internal alkynes, there are very few examples. Aubert has shown that dicobalt hexacarbonyl complexes undergo cycloaddition to deliver the expected products (Scheme 1b), 24,25 and Yamamoto has used borylated internal alkynes as the diene component through a tethering approach (Scheme 1c).…”
mentioning
confidence: 99%
See 3 more Smart Citations